Impact of Urban Agriculture on Household Income in Zambia: An Economic Analysis - Mupeta, Mavis; Kuntashula, Elias; Kalinda, Thomson (Asian Journal of Agriculture and Rural Development, 2020)
The study aimed to empirically determine the impact of urban agriculture on household income in Zambia. The analysis was based on the 2007/2008 Urban Consumption/ Expenditure secondary data collected in Kitwe and Lusaka districts, with a total sample size of 2,682 urban households. The propensity score matching approach is used to estimate the impact of urban agriculture on household income since the method takes into account the systematic differences in socio-economic characteristics between the urban agriculture practicing and non-practicing households by matching from both groups with similar characteristics. Results indicate that urban agriculture has a significant positive effect on household income. The income of households that practiced urban agriculture increased by 13.7% to 19.1%. It implies that urban agriculture has the potential to improve household livelihood through enhanced income.